Solid phase extraction methodology for UPLC‐MS based metabolic profiling of urine samples. Issue 18 (6th July 2015) - Michopoulos, Filippos; Gika, Helen; Palachanis, Dimitrios; Theodoridis, Georgios; Wilson, Ian D.; Barbas, Coral
<x xml:space="preserve">Abstract</x> In general, when performing untargeted metabolic phenotyping (metabolomics/metabonomics) studies on biological samples for example urine or food, sample preparation should be kept to a minimum. However, there are circumstances when desalting, preconcentration, or the fractionation of samples into polar and nonpolar metabolites is of value for enabling the subsequent analysis. Because of its simplicity and ease of automation SPE is well suited to such applications prior to analysis by ultra‐performance LC‐TOF‐MS. In the present study, the properties of a range of SPE phases have been investigated with respect to the range of metabolites that can be extracted from urine. The phases include alkyl modified (C8 and, C18‐OH and C18) silica and polymeric materials. The results show that the C18 phase was well suited to fractionating urine into samples suitable for separate analysis of polar and nonpolar constituents via HILIC and RPLC, respectively, while the polymeric materials were best for concentrating and desalting samples.